2018
DOI: 10.3389/fvets.2018.00198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spleen Transcriptome and Immunity Against Avian Colibacillosis After Immunization With Recombinant Attenuated Salmonella Vaccine Strains

Abstract: Avian pathogenic Escherichia coli (APEC) causes extraintestinal infections in poultry. Vaccines targeting APEC in chickens have been partially successful, but many lack heterologous protection. Recombinant attenuated Salmonella vaccine (RASV) strains can induce broad immunity against Salmonella and be modified to deliver E. coli antigens. Along with vaccine characteristics, understanding the host response is crucial for developing improved vaccines. The objectives of this study were to evaluate host responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
(98 reference statements)
0
8
0
1
Order By: Relevance
“…These studies used RASV delivering APEC surface antigens such as the aerobactin receptor IutA ( Chaudhari et al., 2013 ), but protection was only evaluated for a single APEC strain (O2 serotype). Furthermore, RASV has cross-reactivity with Enterobacteriaceae ( Curtiss et al., 2013 ), and our recent studies have demonstrated cross-reactivity between RASV strains and APEC antigens ( Maddux et al., 2017 ) including IutA and the salmochelin receptor IroN ( Stromberg et al., 2018 ). Thus, it is possible these RASV can be used to simultaneously decrease bacterial load of both Salmonella and APEC in chickens.…”
Section: Introductionmentioning
confidence: 89%
“…These studies used RASV delivering APEC surface antigens such as the aerobactin receptor IutA ( Chaudhari et al., 2013 ), but protection was only evaluated for a single APEC strain (O2 serotype). Furthermore, RASV has cross-reactivity with Enterobacteriaceae ( Curtiss et al., 2013 ), and our recent studies have demonstrated cross-reactivity between RASV strains and APEC antigens ( Maddux et al., 2017 ) including IutA and the salmochelin receptor IroN ( Stromberg et al., 2018 ). Thus, it is possible these RASV can be used to simultaneously decrease bacterial load of both Salmonella and APEC in chickens.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, Redweik et al demonstrated white leghorns when fed probiotics and vaccinated with recombinant attenuated Salmonella resulted in significantly lower signs of APEC related airsacculitis, pericarditis/perihepatitis compared to the control [ 170 ]. These vaccines could decrease bacterial load of both Salmonella and APEC through cross-reactivity between recombinant attenuated Salmonella vaccine strains and APEC antigens including iutA and iroN [ 171 , 172 , 173 ].…”
Section: Disease Prevention Strategies In Naementioning
confidence: 99%
“…The assumption was supported by the results that immunization with proteindeficient MOMVs dramatically reduced the survival rate of chickens infected by APEC strains. However, this does not necessarily mean that MOMVs work independently of cellular immunity, as APEC strains cause systemic infections, suggesting that cellular immunity may also play an important role in combating APEC infection [43]. Further studies are needed to determine the importance of humoral and cellular immune responses in MOMVsinduced protection.…”
Section: Discussionmentioning
confidence: 99%